Addressing the Importance of Stem Cell-Based Therapy: A Perspective in the Treatment of COVID-19 - Ibrahim, Christine; Semaan, Hanna; El-Sabban, Marwan; Najjar, Fadia; Hamade, Aline (Current Molecular Medicine, 2021)
Severe acute respiratory syndrome-associated coronavirus 2 (SARS-CoV-2) is an extremely pathogenic virus belonging to the family of Coronaviridae. First identified in Wuhan, China in December 2019 after an epidemiological investigation of an emerging cluster of pneumonia of unknown etiology, SARS-CoV-2 was declared the cause of a pandemic on March 11 by the World Health Organization (WHO), pointing to the over 118000 cases of Coronavirus disease 2019 (COVID-19) in over 110 countries. Despite the promising results of drug repositioning studies in the treatment of COVID-19, the evidence of their safety and efficacy remains inconclusive. Cell based therapy has been proven safe and possibly effective in treating multiple lung injuries and diseases, but its potential use in the treatment of COVID-19 has not been yet elucidated. Our aim in this review is to provide an overview of the immunomodulatory effect and the regenerative capacity of stem cells and their secretome in the treatment of many diseases including lung injuries. Those findings may contribute to a better understanding of the potential of stem cell therapy in SARS-CoV-2 infection and its potential use in order to find a solution for this healthcare crisis.
Keywords: lung injuries